Pelaksanaan Metode Pembiasaan dalam Pembentukan Kedisiplinan Ibadah Shalat Peserta Didik di SDIT Buah Hati Padang - Sepriasa, Anita; Rahman, Rini (Lembaga Yasin AlSys, 2024)
This research aims to determine the implementation of the habituation method in forming students' discipline in praying five times a day. Research data was taken through direct interviews with Islamic religious education teachers, 2 homeroom teachers and 21 students. To strengthen the interview data, the researcher made observations by observing the process of implementing the habituation method, namely midday and Asr prayers in congregation. The results of the research show that there are 3 forms of implementation of the refraction method 1) midday prayer in congregation 2) afternoon prayer in congregation 3) use of monitoring books. In order to get used to noon prayer in congregation at school, all students must carry it out, while for Ashar prayer in congregation only students who have not gone home and for use of monitoring books from grade one to grade six.